PENGARUH KETERAMPILAN MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 2 PROPPO PAMEKASAN - Maliki, Imyal Al; Rijal, Syamsul (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2024)
Learning motivation is expected to be able to inspire students' enthusiasm for learning so that students can excel, research on teaching skills and learning motivation. This research uses quantitative research using the product moment correlation formula. The results of the research show that at SMPN 2 Proppo Pamekasan it produces: 1) There is an influence of the teaching skills of Islamic Religious Education subject teachers on student learning motivation in motivating students to learn at SMPN 2 Proppo Pamekasan. This is proven by hypothesis testing using the Product Moment formula which obtains 0.468 from N = 76 or df = 74. The result "r" of this work is greater than the critical value "r" of the product moment table both in the 5% confidence interval which has a value of 0.325 as well as the 1% confidence interval which has a value of 0.418. (2) The teacher's teaching skills on student learning motivation in Islamic Religious Education subjects on student learning motivation at SMPN 2 Proppo Pamekasan have quite a strong influence. It is proven that the working "r" of 0.468 is in the range of numbers between 0.400 to 0.600 with a fairly strong interpretation. The implications of this research are: 1) Improving the Quality of Teaching, 2) The Role of Motivation in Learning, 3) Developing Teacher Skills, 4) Establishing a Supportive Learning Environment, 5) Using a Varied Teaching Approach.